How to Improve Disaster Governance for Non-Natural Disaster? A Literatur Study Evaluating Indonesian Government Management of Disaster during The Covid-19 Pademic - Oscar Radyan Danar; Suhartono Winoto; Aulia Puspaning Galih (Jurnal Kawistara, 2022)
Infection with the COVID-19 virus since the end of 2019 has become the biggest pandemic tragedy of this century. In a short time, this virus spread throughout the country infecting millions of people and causing an increase in the world's death toll. At the beginning of the spread of COVID-19, government of Indonesia showed no sense of crisis and had weak disaster management system. The response to control COVID-19 impacts in Indonesia is interesting to analyze. This study adopted a quantitative systematic literature review of academic articles on Indonesian government response to the Covid-19 pandemic published in national and international journals. There were four main topics in the study of disaster management, namely government policy, intergovernmental relations, crisis communication phases, and mitigation and preparedness. This study found that that the government had to improve the communication strategies to deliver data of COVID-19 and mitigation strategies to keep COVID-19 under controlled. Thus, it is necessary to develop a model for handling non-natural disasters in the perspective of disaster governance to strengthen interactions between institutions, communication channels in the midst of crisis conditions, and develop emergency response and preparedness procedures.